Study on the Reduction Effect of Stereo Depth Caused by Lens Aberration in Lenticular-Based Autostereoscopic Displays - Ping Su (Applied Sciences, 2019)
Autostereoscopic displays employing lenticular sheets have broad applications due to the high transmittance of lenticular sheet. However, due to the restriction of lens array design and processing, the imperfect image of lenses can reduce the quality experience of autostereoscopic displays. Stereo depth is one of the qualities of experience parameters, which relates to the three-dimensional effect. Therefore, to quantize the reduction effect of stereo depth caused by lens aberration is of great value. In this paper, we implement a binocular model of an autostereoscopic display system with lens array to analyze this effect, which is different from the previously used monocular model. Two receivers in the positions of viewer’s eyes are set on the viewing plane, and a similar factor is defined to evaluate the difference of light spots perceived by the two receivers. When the similar factor exceeds a certain value, the two spots cannot be fused in the brain, thus restricting the perceived stereo depth. Both in simulation and experiment, a sudden decrease of the similar factor is observed when the viewing angle exceeds 16°. In the subjective experiment, all the sixteen viewers feel a sudden decrease of stereo depth when the viewing angle exceeds 16°, which further verifies the validity of the model. The model and the method are significant for improving the viewing experience of autostereoscopic displays and providing a guidance on autostereoscopic display system designing.